The Implementation of English Online Learning in Rural-Area - Muhammad Bambang Purwanto; Despita (Channing : Journal of English Language Education and Literature, 2023)
This article's goal is to explain how well English may be learned online. The research methodology for this study combines qualitative descriptive analytic approaches with descriptive methods. Qualitative research describes in depth and detail and generates data in the form of spoken or written words from the subjects being studied. Through qualitative research methods like in-depth interviews, it is possible to comprehend the behaviors of the subject and object under study. The interview form is conducted online utilizing the WhatsApp app due to online circumstances. 29 students from class VIII of SMP Nur Hidayah, Ulak Embacang, and Musi Banyuasin served as the primary data sources, while secondary data sources included books, journals, and library materials linked to this subject. 26 of the 29 pupils in class VIII at SMP Nur Hidayah Ulak Embacang approved with online learning, according to the results. The others disagreed because their families' circumstances were still less favorable. The discussion leads to the conclusion that online English learning is a very efficient approach for learning the language. It is evident from the accomplishment of the language learning objective, namely the improvement of English language abilities.